1997
DOI: 10.1073/pnas.94.12.6369
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of the human prostate-specific antigen gene in transgenic mice: Implications for tolerance and immunotherapy

Abstract: Human prostate-specific antigen (PSA) has been widely used as a serum marker for cancer of the prostate. The cell type-specific expression of PSA also makes it a potential tumor antigen for prostate cancer immunotherapy. Study of the immunological aspects of PSA within either normal or malignant prostate tissue has been hampered by the lack of a mouse model, because no PSA counterpart has been identified in mice. Using a 14-kb genomic DNA region that encompasses the entire human PSA gene and adjacent f lanking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…16 Two other PSA transgenes were constructed based on a 6 kb promoter/enhancer region 17 and the whole human PSA gene (12 kb), and were reported to be essentially prostate-specific with LacZ as a reporter gene. 17,18 The PSA promoter region has not yet been used to target prostatic function in transgenic mice. 8 The transgenic adenocarcinoma mouse prostate (TRAMP) [19][20][21] and the LPB-Tag 22,23 models are all based on a prostate-specific gene, rat probasin (rPB), for targeting to the prostate and directing the SV40 Tag (SV40 T and t antigens) expression.…”
Section: Psp94 Gene Promoter/enhancer Region-directed Sv40 Tag Expresmentioning
confidence: 99%
“…16 Two other PSA transgenes were constructed based on a 6 kb promoter/enhancer region 17 and the whole human PSA gene (12 kb), and were reported to be essentially prostate-specific with LacZ as a reporter gene. 17,18 The PSA promoter region has not yet been used to target prostatic function in transgenic mice. 8 The transgenic adenocarcinoma mouse prostate (TRAMP) [19][20][21] and the LPB-Tag 22,23 models are all based on a prostate-specific gene, rat probasin (rPB), for targeting to the prostate and directing the SV40 Tag (SV40 T and t antigens) expression.…”
Section: Psp94 Gene Promoter/enhancer Region-directed Sv40 Tag Expresmentioning
confidence: 99%
“…Several of the promoters described above such as rat probasin or mouse C3/PSBP for epithelial cells and cryptdin for neuroendocrine cells will be particularly useful in this regard. In addition, other promoters are emerging for this purpose, including human PSA (Cleutjens et al, 1997;Wei et al, 1997Wei et al, , 1998Willis et al, 1998). Access to candidate genes will be facilitated greatly by human genome mapping, the Cancer Genome Anatomy Project (CGAP), and microarray technology, as well as by gene discovery e orts in chromosomal regions of recurrent prostatetumor associated loss or gain.…”
Section: Future Directionsmentioning
confidence: 99%
“…In fact, lobespeci®c expression of genes in mouse prostate using prostate speci®c promoters (e.g., the probasin promoter (Gingrich et al, 1996;Greenberg et al, 1995;Kasper et al, 1998;Yan et al, 1997) or the prostate-speci®c antigen promoter (Cleutjens et al, 1997;Wei et al, 1997)) was recently shown to be feasible. As C-CAM has a functional role in prostate growth control and C-CAM was mainly expressed in DLP, where prostate cancer frequently occurs, further investigating the role of C-CAM in an in vivo transgenic mouse model will be important.…”
Section: Discussionmentioning
confidence: 99%